Molecular identification of Sarcocystis halieti n. sp., Sarcocystis lari and Sarcocystis truncata in the intestine of a white-tailed sea eagle (Haliaeetus albicilla) in Norway - Gjerde, Bjørn; Vikøren, Turid; Hamnes, Inger Sofie (Zenodo, 2018)
Gjerde, Bjørn, Vikøren, Turid, Hamnes, Inger Sofie (2018): Molecular identification of Sarcocystis halieti n. sp., Sarcocystis lari and Sarcocystis truncata in the intestine of a white-tailed sea eagle (Haliaeetus albicilla) in Norway. International Journal for Parasitology: Parasites and Wildlife 7 (1): 1-11, DOI:10.1016/j.ijppaw.2017.12.001, URL: http://dx.doi.org/10.1016/j.ijppaw.2017.12.001